KONSTRUKSI MAKNA PUNK BAGI ANGGOTA KOMUNITAS PUNK DI KOTA PEKANBARU - Bestari, Darmayuni; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Punk community is a social phenomenon that the plague, punk more famous in this appearance, the appearance of which is very prominent in this community and become characteristic of punk children. What are imposed the son of punk is not without meaning for them is a way to show of solidarity. This research aims to know the motif children become punk punk, son of punk redefining himself as punk and how others (environment) redefining punk.This research uses qualitative research method by doing fenomenologi approach. The subject in this study amounted to 9 . Data collection techniques that are grouped through participant observation, in-depth interviews and documentation. This research uses the model of interactive data analysis Miles and Hubermen, using the technique of checking the validity of the data through an extension of the participation and triangulation.The results of this research showed that the motif punk children to become punk is looking for the meaning of freedom itself, freedom in the sense of solidarity that high against his neighbor, and they were of the independent. Although the way that they do different from other public society, they also always offers to anyone who they come across in the siege to join this community. The true meaning of himself the son of punk redefining punk they realize that people not only know the activities that they have already done for this. Punk for them is the container to continue life, because here they find the life that they do not think they will get from elsewhere. They also assess the positive punk even though viewed negatively by the people they deem not understand what it means to be punk was actually. The true meaning of others (environment : neighbors) redefining punk, namely as a group of concern because of the appearance that is causing negative ratings to their own although in actual fact punk including collection of a good man. But have different ways to dammed up from people in general.Keyword: Construction Meaning , Punk